1999
DOI: 10.1016/s0006-3495(99)77175-4
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Determinants of Binding the rRNA Substrate and Small Ligands to Ricin A-Chain

Abstract: A continuum model is provided of the free energy terms that contribute to the molecular association of ricin A-chain (RTA) with the rRNA substrate and several small ligands. The model for RTA interactions with the RNA was taken from a previously proposed complex containing a 29-mer oligonucleotide hairpin (. Proteins 27:80-95), and models for the ligands were constructed from x-ray crystallographic structures. The calculated absolute free energies of complex formation for the RTA-RNA assembly and several singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…We show here that G212A binds ribosomes and ribosomal stalk similarly as wild type RTA but depurinates ribosomes and RNA at a lower catalytic rate than wild type RTA. Gly 212 is located between Trp 211 , which is involved in binding to the target adenine (60,61), and Arg 213 , which contributes to binding to the rRNA (62,63) and is on the opposite side from the RTA/RTB contacts (Fig. 2B).…”
Section: Discussionmentioning
confidence: 99%
“…We show here that G212A binds ribosomes and ribosomal stalk similarly as wild type RTA but depurinates ribosomes and RNA at a lower catalytic rate than wild type RTA. Gly 212 is located between Trp 211 , which is involved in binding to the target adenine (60,61), and Arg 213 , which contributes to binding to the rRNA (62,63) and is on the opposite side from the RTA/RTB contacts (Fig. 2B).…”
Section: Discussionmentioning
confidence: 99%
“…The lower adherence found with phosphate buffer may have been due at least in part to the natural affinity of RTA for phosphate groups in its rRNA substrate [28]. Association of phosphate ions with the protein could alter its surface properties, affecting interactions with the adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, many calculations have found that electrostatic interaction energies between proteins and nucleic acids are positive, meaning that electrostatic interactions are destabilizing for their binding (see Table I). [3][4][5][6][7][8][9][10][11][12][13] These calculation results are very counterintuitive. They were obtained from solving the PoissonBoltzmann (PB) equation by choosing the molecular surface as the boundary between the solute low dielectric and the solvent dielectric.…”
Section: Introductionmentioning
confidence: 99%